Improvement in the performance of the vortex flowmeter using contraction cone. (December 2017) - Mohadikar, Kapil; Venugopal, A.; Agrawal, Amit; Prabhu, S.V.
Highlights: Contraction cone is installed upstream to the bluff body of vortex flowmeter. It is found that contraction cone helps in extending the lower operating range. A turndown ratio of 1:80 is achieved with contraction cone. Upstream developing length requirement for vortex flowmeter is reduced. Abstract: The present experimental study investigates a new configuration of vortex flowmeter to improve the turndown ratio and flow distortion sensitivity. An optimized contraction cone is introduced upstream to the vortex shedder to enhance the strength of the shed vortices and to suppress upstream flow distortion effects. A trapezoidal bluff body with two different blockage ratios (19% and 28%) is studied as a vortex shedder. The performance of this new configuration is studied under fully developed flow condition and also evaluated with various flow disturbances. The flow distortion is introduced with 90° degree in-plane and out-of-plane elbows. Transient wall pressure measurement technique is used to capture the vortex shedding frequency. It is found that 28% blockage ratio with optimized contraction cone is the best combination to improve the turn down ratio of vortex flowmeter. The installation of contraction cone helps in reducing the non-uniformity in the velocity profiles which improves the strength and stability of the shed vortices. Minimum measurable Reynolds number obtained with this technique is 5000 which is significantly lower than conventional vortex flowmeters. The turn down ratio achieved with this technique is 1:80 as opposed to 1:20 for conventional vortex flowmeters.